Shipwreck Archaeology in China Sea - Song, Jianzhong (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book initiatively and systematically presents the latest discoveries in the context of shipwreck archaeology in China, telling the exciting story of the wrecks' distribution, connotation and the research advances and empirically reconstructing the development of overseas trade and maritime cultures along the Maritime Silk Road, which flourished for more than 2000 years. The book features numerous high-quality images and comprehensively describes and reviews the development of the methodologies and technologies used in China's underwater archaeology and underwater cultural heritage administration in recent decades.
Introduction: Archaeological Discovery and Research of Ancient Shipwrecks in China in last thirties Years -- Chapter 1 Shipwreck of the Yuan Dynasty investigated at Sandaogang, Suizhong, Liaoning -- Chapter 2 Shipwrecks of the Yuan and Ming Dynasties discovered at Penglai , Yantai, Shandong -- Chapter 3 Ancient Shipwrecks Excavated in Ningbo, Zhejiang Province -- Chapter 4 Dinghai Bay Shipwrecks of Yuan and Ming dynasties in Lianjiang of Fujian -- Chapter 5 Ancient Shipwrecks Investigated off the Pingtan Island and Nanri Islands, Fujian Province -- Chapter 6 Song Dynasty Shipwreck excavated in Quanzhou Bay of Fujian -- Chapter 7 Ancient Shipwrecks Off the Coast of Zhangzhou, Fujian -- Chapter 8 Nanhai No 1 Shipwreck off Yangjiang coast of Guangdong -- Chapter 9 Ming Dynasty Shipwrecks Discovered in Nan'ao and Shantou, Guangdong -- Chapter 10 Ancient Shipwrecks Discovered in the Waters of the Xisha Islands -- Chapter 11 The Shipwreck Archaeology in the Waters of Taiwan, Penghu and Dongsha Island.
Keywords: Underwater archaeology; Cultural property; Archaeology; Archaeology-Methodology.; Civilization-History.; Maritime Archaeology; Archaeology and Heritage; Archaeological Methodology; Cultural History